2023
DOI: 10.47391/jpma.akus-06
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of cancer stem cell biomarkers in oral squamous cell carcinoma; A Systematic Review

Abstract: Objective: To evaluate the role of cancer stem cell biomarkers in diagnosis and prognosis of OSCC patients. Methods: The search strategy was entered into PubMed NLM, EBSCO CINAHL, EBSCO Dentistry & Oral Sciences Source, Wiley Cochrane Library, and Scopus. The full text eligible studies (n=7) were assessed for their quality using the JBI Critical Appraisal Checklist to evaluates the methodological quality of the studies based on possibility of bias in its design, conduct, and analysis. Selected studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…High expression levels of heat shock proteins may be associated with worse prognostic pictures. Thus, having these data available could be crucial for optimizing the individual therapy of individuals with carcinoma [23][24][25][26]. Recent studies have revealed the crucial role of HSPs in maintaining cellular stability and averting programmed cell death (apoptosis).…”
Section: Introductionmentioning
confidence: 99%
“…High expression levels of heat shock proteins may be associated with worse prognostic pictures. Thus, having these data available could be crucial for optimizing the individual therapy of individuals with carcinoma [23][24][25][26]. Recent studies have revealed the crucial role of HSPs in maintaining cellular stability and averting programmed cell death (apoptosis).…”
Section: Introductionmentioning
confidence: 99%